ENHANCING EFL READING COMPREHENSION THROUGH CHUNKING STRATEGIES: CLASSROOM RESEARCH IN VOCATIONAL EDUCATION - Nurul Aminatus Zuhriya; Lailatul Musyarofah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Indonesian vocational EFL students still have problems understanding reading materials. Students tend to base their understanding on word analysis and translation, which hinders their ability to read texts as a whole. This problem is particularly critical as students need to understand instructional and procedural texts for their work. This study aimed to apply the chunking strategy to improve students' reading comprehension in vocational EFL classes. Using the CAR method, which focuses on a group of vocational high school students, this study was conducted in a single cycle comprising four stages: planning, implementation, observation, and reflection. Reading comprehension tests, classroom observations, and student reflection notes were used as data collection instruments. A significant improvement in students' reading comprehension, as evidenced by higher test scores, increased reading fluency, and changes in the reading process, which initially involved only looking at groups of words or phrases to construct meaning. Classroom observations showed an improvement in students' participation and confidence. Some students did not show their improvement, but their scores did not decline either. This condition shows that the strategy was quite effective in teaching them. The study was terminated at the end of cycle I because the teaching objectives had been achieved. This study provides practical evidence of the effectiveness and feasibility of the chunking strategy in improving reading comprehension in a vocational school setting. ABSTRAK Siswa EFL di sekolah kejuruan Indonesia masih mengalami kesulitan dalam memahami bahan bacaan. Siswa cenderung mendasarkan pemahaman mereka pada analisis kata dan terjemahan, yang menghambat kemampuan mereka untuk membaca teks secara menyeluruh. Masalah ini sangat kritis karena siswa perlu memahami teks instruksional dan prosedural untuk keperluan pekerjaan mereka. Penelitian ini bertujuan untuk menerapkan strategi chunking guna meningkatkan pemahaman membaca siswa di kelas EFL sekolah kejuruan. Dengan menggunakan metode CAR, yang berfokus pada sekelompok siswa sekolah menengah kejuruan, penelitian ini dilakukan dalam satu siklus yang terdiri dari empat tahap: perencanaan, pelaksanaan, observasi, dan refleksi. Tes pemahaman bacaan, pengamatan kelas, dan catatan refleksi siswa digunakan sebagai instrumen pengumpulan data. Terjadi peningkatan signifikan dalam pemahaman bacaan siswa, yang dibuktikan dengan nilai tes yang lebih tinggi, peningkatan kelancaran membaca, dan perubahan dalam proses membaca, yang awalnya hanya melibatkan melihat kelompok kata atau frasa untuk membangun makna. Pengamatan kelas menunjukkan peningkatan partisipasi dan kepercayaan diri siswa. Beberapa siswa tidak menunjukkan peningkatan, namun skor mereka juga tidak menurun. Kondisi ini menunjukkan bahwa strategi tersebut cukup efektif dalam mengajar mereka. Penelitian ini dihentikan pada akhir siklus I karena tujuan pembelajaran telah tercapai. Penelitian ini memberikan bukti praktis mengenai efektivitas dan kelayakan strategi chunking dalam meningkatkan pemahaman bacaan di lingkungan sekolah kejuruan.